Performance fuzzy analytical hierarchy process to identify drought areas for disaster mitigation - Aprillya, Mala Rosa; Ardyansyah, Heri (Institute of Advanced Engineering and Science, 2023)
Drought causes crop failure in the agricultural sector and a limited supply of clean water. Land damage due to drought in Lamongan has reached ±12,000 ha in the last decade. The lack of information regarding drought disaster mitigation resulted in quite large losses in several agricultural sectors. The purpose of this study is to develop a decision support system (DSS) that can provide information regarding the identification of drought-prone areas. The fuzzy analytical hierarchy process (FAHP) method is implemented with four criteria: rainfall intensity, slope, soil type, and distance to the river. FAHP is good for processing the weighting of several criteria and categories to produce good choices. Results, the tests carried out there were 20 sub-districts prone to drought, with an accuracy rate of the FAHP method of 85%. The average value of respondent satisfaction averaged 97.2%. DSS application can provide the status of areas prone to drought. For future studies, the temperature and evapotranspiration parameters can be added, to provide better results.